Can teachers use assessment to improve learning? (Práxis Educativa, 2009)
This article discusses two different purposes of assessment: formative assessment is designed to support pupils’ learning, whilst summative assessment is designed to review what has been learnt, perhaps to record it in certificates or diplomas. Formative assessment is concerned with the frequent interactions between teacher and pupils which are essential if the teacher’s plans can be matched to the learning needs of the pupils. Teachers who are accustomed to simply telling pupils, rather than engaging them in dialogue, find it hard to change. Pupils also have to change from passive reception to active engagement in the learning. Formative work can be undermined if pupils or teachers are worry too much about summative tests; such worry can lead them to focus entirely on practising for the tests and not on the good habits of learning which would in fact be the best preparation for doing well in them. Keywords: Formative assessment. Summative assessment. Tests.